Perhitungan Luas Daun Tanaman Kayu Putih (Melaleuca leucadendra) dengan Manual dan Digital (ImageJ) - Umam, Choirul; ‘Uluwiy, Abdurrahman; Auliya, Rohmatul; Putri, Ratna Nurshakti; Alwi, Muhammad Tsabit (Jurnal Ilmiah Teknologi Pertanian Agrotechno; Vol 9 No 2 (2024)DO - 10.24843/JITPA/2024.v09.i02.p02, 2025)
Leaves are essential plant organs and the main parameters for analyzing plant growth. One of the important plants in Indonesia is the eucalyptus plant, which is widely used as the main ingredient of essential oils worldwide. Speed and accuracy are crucial in measuring leaf area. This research is expected to be an alternative to practical and calibrated leaf area measurements because the calculation process is carried out automatically through images and processed by the application. This research was conducted in March 2024 at the Biotechnology and Plant Physiology Laboratory of the Agroecotechnology Study Program, Faculty of Agriculture, Trunojoyo University Madura. The tools and materials used in this research are a Canon 300D camera, stationery, Asus X441M Intel(R) Celeron(R) N4000 CPU 1.10 GHz RAM 4GB laptop, plastic bag, ImageJ device, and eucalyptus leaf samples. This study uses eucalyptus leaves obtained from 7 eucalyptus trees found in several villages in Bangkalan Regency, East Java. Based on the study's results, it can be concluded that image analysis using ImageJ software on Eucalyptus leaves proved to be more practical and efficient compared to manual methods, namely millimeter blocks and gravimetry. Leaf measurement using ImageJ is feasible to use and develop based on the results of this study and previous studies. The average error value of leaf measurement using ImageJ against the millimeter block method is 8.46% with a correlation value of 0.9353, while the measurement of leaf area using ImageJ against the gravimetric method is 47.31% with a correlation of 0.7328. This shows a powerful attachment to the millimeter block method and robustness to the gravimetric method